Several new combinations from previous Didymocarpus to Palmatiboea (Gesneriaceae) - Fang Wen; Qiang Fan (PhytoKeys)
The recently published species, Didymocarpus pingyuanensis, is transferred here to the recently re-circumscribed genus, Palmatiboea. Two varieties, recently assigned to Palmatiboea, have been raised to the rank of species. Their Chinese vernacular names are also revised and provided here.